2015
DOI: 10.1542/peds.2014-0628
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Depressive Symptoms During Childhood and Risky Adolescent Health Behaviors

Abstract: OBJECTIVE: Maternal depression is a risk factor for adolescent depression; however, the effect of childhood exposure to maternal depression on adolescent engagement in health risk behaviors (eg, substance use, delinquency) is unclear. METHODS:We examined the relationship between maternal depressive symptoms (child's age 4-15) and engagement in health risk behaviors at age 16 to 17 by using data from 2910 mother-youth pairs in a nationally representative prospective Canadian cohort. Maternal depressive trajecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 32 publications
1
26
2
2
Order By: Relevance
“…They also found that a high-chronic trajectory in mothers was associated with lower behavioral competence in children relative to the low stable class. Wickham et al (2015) found that maternal depressive symptom trajectories, particularly trajectories with high symptoms during middle childhood, were associated with risky health behaviors in adolescent offspring including common and illicit drug use, nonviolent delinquent behavior and violent delinquency.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…They also found that a high-chronic trajectory in mothers was associated with lower behavioral competence in children relative to the low stable class. Wickham et al (2015) found that maternal depressive symptom trajectories, particularly trajectories with high symptoms during middle childhood, were associated with risky health behaviors in adolescent offspring including common and illicit drug use, nonviolent delinquent behavior and violent delinquency.…”
Section: Resultsmentioning
confidence: 97%
“…The majority of the studies included information on both males and females, however 7 studies included only female participants (Byers et al, 2012; Campbell, Matestic, von Stauffenberg, Mohan, & Kirchner, 2007; Gross, Shaw, Burwell, & Nagin, 2009; Luoma, Korhonen, Salmelin, Helminen, & Tamminen, 2015; Matijasevich et al, 2015; van der Waerden et al, 2015; Wickham, Senthilselvan, Wild, Hoglund, & Colman, 2015) and one study only included male participants (Stoolmiller, Kim, & Capaldi, 2005). The most common measure of depressive symptoms was the Centers for Epidemiologic Studies Depression Scale (CES-D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, the remaining studies that examined gender in the relationship between MDD/depressive symptoms and smoking behavior found that depressed boys and girls reported significantly higher rates of ever and current smoking than those without depression (49)(50)(51)(52). Finally, a recent nationally representative prospective Canadian study (54) found that adolescents exposed to maternal depressive symptoms in middle childhood were significantly more likely to ever smoke and to initiate smoking at an earlier age than adolescents exposed to few maternal depressive symptoms.…”
Section: Adolescentsmentioning
confidence: 99%
“…Por esta razón, desde el nacimiento empieza la relación interpersonal más importante, en la cual la madre provee a los neonatos de los cuidados necesarios para sobrevivir y madurar (Alsina-Llanes, Brun & Olazábal, 2015;Wickham, Senthilselvan, Wild, Hoglund & Colman, 2015), y, al mismo tiempo, regula las respuestas emocionales que favorecen el adecuado crecimiento y desarrollo cognitivo (atención, memoria, aprendizaje, etc. ) de los recién nacidos (Kristal, 2009).…”
Section: Introductionunclassified